Nucleases that degrade extracellular DNA of bacterial biofilms - А.Е. Abaturov (Zaslavsky O.Yu., 2020)
Extracellular bacterial DNA (eDNA) is actively involved in the formation and vital activity of biofilms, acting as a major structural component of the matrix. The release of eDNA into the biofilm continuum is due to bacterial cell lysis and active secretion by a lysis-independent mechanism. Molecules of eDNA are present in species-specific amounts in biofilms of different microorganisms and are organized as clear morphological formations forming mesh structures or filamentous networks. The importance of eDNA in maintaining matrix stability is particularly high in the early stages of biofilm development. EDNA is involved in biofilms: as a factor contributing to bacterial adhesion, biofilm formation, and extracellular matrix production; as a structural component in ensuring matrix stability; as a substrate for the process of gene transfer through transformation of competent sister bacteria; as a nutrient and as a protective factor of bacterial biofilms. Reducing the content of eDNA destabilizes the matrix, which promotes the release of bacteria from biofilms and, as a consequence, increases the sensitivity of pathogens to the action of antibacterial agents. Cleavage of eDNA molecules by DNase is one of the ways of degradation of the biofilm matrix and overcoming bacterial antibiotic resistance associated with biofilm formation. It has been shown that DNases, in particular DNase I, DNase 1L2, NucB nuclease, effectively destroy young biofilms of different Gram-negative and Gram-positive bacteria. Currently, DNases are considered as possible models of future antibiofilm drugs. Given the lack of long-term activity and the limited depth of penetration in the dispersion of biofilms of these drugs, a nanotechnological DNA mimetic artificial enzyme was developed and synthesized, which has a high level of DNase-like antibiofilm activity. In the clinical practice, highly purified human recombinant DNase I - dornase alpha - is being successfully used in the treatment of infections in patients with cystic fibrosis.